1991
DOI: 10.1073/pnas.88.5.1775
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis toxin-sensitive G proteins are transported toward synaptic terminals by fast axonal transport.

Abstract: We rind that half of the pertussis toxinsensitive guanine nucleotide-binding protein (G protein) in the squid (Loligo pealei) giant axon is cytoplasmic and that this species of G protein is intermediate in size between the two forms present in axolemma. This G protein is transported toward synaptic terminals at 44 mm/day. Moreover, these data are consistent with there being two additional steps leading to the maturation of G proteins: (i). association with and transport on intracellular organelles and (ii) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In experiments described here, various probes for GTP-binding proteins, and broad spectrum inhibitors of protein kinases or phosphatases were added to the perfusion buffer, and the effects on organelle transport velocity were monitored by quantitative video microscopy. Prior studies have demonstrated the presence of such regulatory proteins in squid axoplasm (22,37,82). The results of the current studies imply that fast axonal transport is modulated by cycles of GTP hydrolysis and nucleotide exchange by one or more species of GTP-binding protein.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…In experiments described here, various probes for GTP-binding proteins, and broad spectrum inhibitors of protein kinases or phosphatases were added to the perfusion buffer, and the effects on organelle transport velocity were monitored by quantitative video microscopy. Prior studies have demonstrated the presence of such regulatory proteins in squid axoplasm (22,37,82). The results of the current studies imply that fast axonal transport is modulated by cycles of GTP hydrolysis and nucleotide exchange by one or more species of GTP-binding protein.…”
supporting
confidence: 55%
“…Proteins that are known to bind guanine nucleotides and have been implicated in regulation of membrane traffic include numerous heterotrimeric G-proteins and small GTP-binding proteins, as well as dynamin. Pertussis toxin-sensitive G-proteins are known to be present in squid axoplasm (82), and to test whether the effects of GTPTS on fast axonal transport might be due to these or other G-proteins, axons were perfused with AIF4-. This salt, which is formed by mixing low concentrations (1-100 #M) of A1CI3 with higher concentrations (5-30 mM) of KF or NaF, mimics the effects of GTPTS on all known heterotrimeric G-proteins, but does not affect small GTP-binding proteins (34,74).…”
Section: Potential Targets For Gtptsmentioning
confidence: 99%
“…We do not know the mechanisms that govern this translocation. In squid growth axons, G proteins that are pertussis toxin substrates can be transported distally by fast axonal transport (Vogel et al, 1991). In some PC12 cells that have not yet differentiated or are in early stages of response to NGF, a,, immunoreactivity is localized to filopodial protrusions or developing processes.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we have examined whether such a transduction mechanism may exist in the neuron, whereby GTPbinding proteins may also be activated to leave the cell membrane to become stable second messengers transported from the axon tip to the cell body. A recent report has shown the orthograde movement of pertussis toxin substrates in squid giant axon (Vogel et al, 1991).…”
Section: Introductionmentioning
confidence: 99%